2019
DOI: 10.1002/andp.201900159
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐Dependent Quantum Correlation in a Cavity‐Atom System

Abstract: A scheme to manipulate quantum correlation between output lights of a cavity-atom system by phase control is proposed. A driving-field phase is introduced which has a similar value with that of building up quantum correlation in a Hanbury-Brown-Twiss setup. A closed-loop phase is formed to improve quantum coherence by phase-dependent electromagnetically induced transparency. The closed-loop phase has been utilized to realize quantum correlation and even quantum entanglement in the atomic system of previous wor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…[17,25] Consequently, it is crucial to manipulate and obtain stable quantum correlation for the development of quantum technology. [26] In one of our previous studies, [27] it is shown that the secondorder intensity correlation is also modified by the relative phase of the input probe fields, and the maximum stable correlation is attained when the relative phase is equal to 𝜋. In this paper, it is revealed that the maximum stable correlation is also generated in spite of zero relative phase, and the controllable secondorder intensity correlation is realized by a coherent coupling laser and an incoherent pumping field in a three-level atom-cavity system.…”
Section: Introductionmentioning
confidence: 88%
“…[17,25] Consequently, it is crucial to manipulate and obtain stable quantum correlation for the development of quantum technology. [26] In one of our previous studies, [27] it is shown that the secondorder intensity correlation is also modified by the relative phase of the input probe fields, and the maximum stable correlation is attained when the relative phase is equal to 𝜋. In this paper, it is revealed that the maximum stable correlation is also generated in spite of zero relative phase, and the controllable secondorder intensity correlation is realized by a coherent coupling laser and an incoherent pumping field in a three-level atom-cavity system.…”
Section: Introductionmentioning
confidence: 88%